Evaluation of Post-Extraction Healing Using Platelet-Rich Fibrin Versus Conventional Healing: A Comparative Clinical Study (Academia Journal of Medicine, 2026)
Background: Post-extraction wound healing is an important determinant of patient  comfort and successful oral rehabilitation. Platelet-Rich Fibrin (PRF), a second-generation  platelet concentrate, has gained considerable attention because of its potential to accelerate  soft-tissue healing and reduce post-operative complications due to the sustained release of  growth factors. Aim: To comparatively evaluate post-extraction healing in extraction sockets treated with  PRF and conventional healing following routine dental extraction. Materials and Methods: This randomized clinical study was conducted among 30 patients  requiring bilateral extraction of comparable teeth. The patients were divided into two  groups: Group I (PRF group), where PRF was placed into the extraction socket immediately  after extraction, and Group II (control group), where extraction sockets were allowed to  heal conventionally without any adjunctive material. Clinical parameters including pain,  swelling, soft-tissue healing, and incidence of complications were assessed on the 1st, 3rd,  and 7th post-operative days using standardized indices and visual analogue scale (VAS). The  collected data were statistically analyzed using appropriate tests with significance set at p
Keywords: Platelet-Rich Fibrin, Wound Healing, Post-operative Pain, Soft-Tissue Healing